Attenuation technique for measuring sediment displacement levels - Munro, Richard J.; Dalziel, Stuart B. (Springer, 2005)
A technique for obtaining accurate, high (spatial) resolution measurements of sediment redeposition levels is described. In certain regimes, the method may also be employed to provide measurements of sediment layer thickness as a function of time. The method uses a uniform light source placed beneath the layer, consisting of transparent particles, so that the intensity of light at a point on the surface of the layer can be related to the depth of particles at that point. A set of experiments, using the impact of a vortex ring with a glass ballotini particle layer as the resuspension mechanism, are described to test and illustrate the technique.